U.P. changing visions ; "349" ; Saving eagles [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1993)
Tackles protest against the appointment of Emil Javier as UP new President, the Senate Bill no. 1305 Consumer Act of the Philippines penalizing fraud and deception of marketing promotion. The Pepsi 349 movement is gaining legal grounds. Tackles also the baby eagle, Pagasa. The Philippine Eagle Propagation Program receives extensive financial support.
Contents : U.P. : changing visions (17 min.) -- "349" (14 min.) -- Saving the eagles (12 min.).
Reporter, Luchie Cruz-Valdes.
Keywords: University of the Philippines (Diliman).; Birds -- Philippines -- Davao City; Consumer protection -- Law and legislation -- Philippines; Sales promotion -- Philippines